Penggunaan Teknologi Hidroponik dalam Budidaya Sayuran di Era Generasi Muda: The Use of Hydroponic Technology in Vegetable Cultivation in the Era of the Young Generation - Fitriyani, Nurzalifa; Rozaki, Zuhud; Wulandari, Retno; Suryani, Cahyaningrum Arie (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
This article explores the utilisation of hydroponic technology in vegetable cultivation among the younger generation. It aims to determine the factors that influence the interest of the younger generation in using hydroponic technology for vegetable cultivation, as well as the challenges, advantages and disadvantages of the method. In addition, it examines the potential business opportunities associated with the use of hydroponic technology. The research methodology used in this study involved the use of secondary data and data analysis techniques. The research findings show that there are several factors that influence the interest of the younger generation in utilising hydroponic technology for vegetable cultivation. These factors include environmental concerns, limited space availability, and the desire for organic and sustainable food production. Furthermore, the research revealed that hydroponic technology offers various advantages, such as efficient water usage and higher yields. However, it also poses certain challenges, including initial investment costs and the need for proper maintenance. The study concluded that the utilisation of hydroponic technology in vegetable cultivation provides a huge business opportunity. The demand for hydroponic vegetables continues to increase, along with the increasing public awareness of the importance of consuming healthy and quality vegetables. In addition, hydroponic technology can also be used for the cultivation of various types of vegetables, so the business opportunities are vast. The findings of this study contribute to the existing knowledge by highlighting the factors that influence the younger generation's interest in hydroponic technology and provide insights into the challenges, advantages and disadvantages, methods, and business opportunities in the use of hydroponic technology.